Assessing the Safety and Efficacy of Trifarotene in the Treatment of Acne Vulgaris - Brumfiel, Caitlin M (Ther Clin Risk Manag, 2021)
Acne vulgaris is a common skin condition of the face and trunk that negatively impacts quality of life. Trifarotene is a new first-in-class fourth-generation topical retinoid that has been uniquely studied in the treatment of both facial and truncal acne. Through selective agonism of retinoic acid receptor (RAR)-gamma, the most predominant RAR isotype in the epidermis, trifarotene exerts more targeted, skin-specific effects than earlier generation retinoids. This narrative review summarizes all currently available literature regarding the use of trifarotene in acne vulgaris. We focus on efficacy, safety, and tolerability data and highlight quality of life outcomes and patient-reported satisfaction. Future clinical trials and the clinical applicability of this novel medication in the treatment of acne are also discussed.